Algoritma Levenshtein Distance sebagai Solusi Efisiensi Pencarian pada Training Registration System - Iqbal Faris Akbar; Mugiarso; Khairunnisa Fadhilla Ramdhania; Rasim (Journal of Students‘ Research in Computer Science, 2024)
The training registration process at Company XYZ faced several challenges, including the use of physical documents, slow file submission, non-standardized document numbering, and inefficient file storage. This research aimed to develop a web-based application called "Training Registration System" using the Waterfall software development method to address these issues, as well as implementing the Levenshtein Distance algorithm in the search feature to enhance training search efficiency. The results showed that the application successfully improved the efficiency and accuracy of the training registration and search process by eliminating the need for physical file submission, accelerating the workflow, and reducing the potential for errors. The implementation of the Levenshtein Distance algorithm also proved effective in improving the efficiency of training searches based on training names, even in cases of typos, such as the strings "Trainning" and "Training" which had a similarity score of 87.5% based on similarity weight calculations.